Isolation and Evaluation of the Antioxidant Capacity of Compounds from Ehretia asperula Zoll. & Moritzi - Duc, Chong Kim Thien; Linh, Tran Chi; Thanh, Nguyen Quoc Chau; Nhien, Pham Quoc; Trang, Dai Thi Xuan; Danh, Luu Thai; Tuan, Nguyen Trong (Universitas Gadjah Mada, 2024)
Ehretia asperula Zoll. & Moritzi was a common medicinal herb found in several Asian nations. This herb was found in many provinces in northern Vietnam, especially Hoa Binh province. Leaves of E. asperula cultivated in Tay Ninh Province were used to isolate compounds and evaluate their potential as antioxidants by five methods, including TAC, RP, FRAP, DPPH, and ABTS•+. Seven compounds were isolated and elucidated from the ethyl acetate fraction, including kaempferol (1), astragalin (2), nicotiflorin (3), rutin (4), caffeic acid (5), (-)-loliolide (6), and daucosterol (7), where compounds 1, 4, 6, and 7 were found from this species for the first time. All isolated compounds from E. asperula leaves exhibited antioxidant activity, consisting of 5.70 ± 0.01 to 299.13 ± 10.19 μg/mL for EC50 values. Especially compound 5 had a very strong antioxidant effect based on five methods TAC (EC50 = 8.43 ± 0.15 μg/mL), RP (EC50 = 6.79 ± 003 μg/mL), FRAP (EC50 = 12.72 ± 006 μg/mL), DPPH (EC50 = 5.57 ± 0.02 µg/mL), and ABTS•+ (EC50 = 5.70 ± 0.01 μg/mL). From our results, Tay Ninh Province's E. asperula leaves are abundant in naturally occurring antioxidants, indicating their potential use as therapeutic materials.